Strengthening The Social Competence Of Final Year Students Through The Field Da’wah Practice Program (PDL) Based On Project-Based Learning - Abu Darda; Mispullah Prihatini (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the strengthening of social competence in final-year santri through the implementation of the Field Da’wah Practice Program (PDL) based on Project-Based Learning (PBL) at PPTQ Qoryatul Qur’an Sukoharjo. This research employs a qualitative case study approach focusing on the implementation of PDL as a project-based learning model and its contribution to the development of santri’s social competence. Data were collected through interviews, observations, and documentation involving pesantren leaders, program supervisors, and final-year santri, and analyzed using Miles and Huberman’s interactive model supported by triangulation techniques. The findings indicate that PDL reflects the core stages of PBL, including problem identification, project planning, implementation, monitoring, and evaluation. Each stage contributes to the development of key social competencies, such as communication skills, interpersonal awareness, emotional regulation, leadership, and responsibility.